Budaya Terapi Lancang Dalam Penyembuhan Pasien Gangguan Mental Di Kalangan Masyarakat Melayu - Fitria, Ayu; Samosir, Hasrat Efendi; Saragi, Muhammad Putra Dinata (An-Nadwah, 2023)
This study aims to find out: (1) How is the culture of lancang therapy in healing patients with mental disorders in Panipahan Village, Riau. (2) What are the forms of mental disorders that require the Panipahan community to carry out lancang therapy. (3) What are the supporting factors and obstacles in carrying out lancang therapy in Panipahan Village, Riau. This study used a qualitative method with a type of field research (field research). Data collection techniques using observation, interviews, and documentation. There were 4 informants in this study, namely 1 Bomoh, 2 Patients and 1 Religious Leader. The results of this study indicate (1) The culture of lancang therapy in Panipahan Darat, Riau is an alternative treatment that has been passed down for generations which is believed to be able to cure several mental disorders through the intermediary of a shaman/bomoh. This treatment is done because of a disease that is believed to be a disturbance of the jinn/demons, then the meaning of this treatment is to feed the jin/demons so they don't interfere. (2) The forms of mental disorders that require the people of Panipahan Darat to take lancang therapy, namely schizophrenia, schizotypal disorders, delusional disorders, mood disorders, neurotic disorders, and behavioral syndromes. (3) The supporting factors in carrying out pre lancang therapy are suggestions and hereditary factors. Inhibiting factors in carrying out lancang treatment such as equipment that should not be lacking and also the presence of shirk.